KONSEP ÃÅ MBAT DALAM KARAWITAN JAWA - Hastanto, Sri (PANGGUNG, 2012)
ÃÅ mbat is one of the musical concept in Javanese gamelan music Ã¢â¬â karawitan Jawa. It is a kind of musical characteristic of a gamelan ensamble ÃÂ which is generated by its interval structure Ã¢â¬â Jv. jangkah Ã¢â¬â ofÃÂ  that gamelan. The only way to understand ÃÂªmbat, one may investigateÃÂ  gamelan tuning system. ÃÅ mbat had been metioned in old Javanese manuscripts including Centhini and WÃÂ©dhapradangga. Kunst and Hood also discussed ÃÂªmbat in some extend, but the result does not quite fit to reality. This work aims to explain the concept of ÃÂªmbat from the angle of the culture owner Ã¢â¬â Javanese.In order to explain the concept, this study has firstly to discover the concept of pitch in karawitan Jawa, secondly the tolerance of the limit in sifting tones , and finally approaching the main goal: the concept of ÃÂªmbat it self. To reach the goal this studi conducted some simple experiments.ÃÂ Key words:structure of jangkah, tolerance of sifting notes,ÃÂ  and ÃÂªmbat